Activités antiradicalaires et étude des composés volatils de trois plantes de la médecine traditionnelle du Bénin: Anchomanes difformis, Parkia biglobosa et Polyalthialongifolia - Akibou, Osseni Moukimou; AGBANGNAN, DOSSA COKOU PASCAL; BOSSOU, Bertin; AVLESSI, FÉLICIEN; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2014)
ABSTRACT: The present study was devoted to the chemical analysis of three plants (Anchomanes difformis, Parkia biglobosa and Polyalthia longifolia) commonly used by traditional healers in Benin, for their curative properties in the treatment of certain diseases. After characterization of large chemical groups present in the leaves of these plants, total polyphenols, condensed tannins, total flavonoids, anthocyanins and anthocyanidins were quantified by spectrophotometric methods. The scavenging activity was evaluated by the DPPH method and the volatile compounds in the powders of these plants were determined by SPMEGC/ MS. The results showed the presence of several secondary metabolites such as saponins, alkaloids, tannin, mucilages, anthraquinones, leucoanthocyanins, anthocyanins and triterpennoids in varying proportions in the three plants. The levels of condensed tannins, total flavonoids and anthocyanins are respectively higher in leaves of P. longifolia (22.5 mg/g, 15.69 mg / g and 0.94 mg/g) than in those of P. biglobosa (16.48 mg/g, 12.03 mg/g and 0.38 mg/g) and that of A. difformis (9.74 mg/g 4.59 mg/g and 0 mg/g ). Against by the total polyphenol content P.longifolia leaves (2.89 mg/g) is between those of A. difformis (2.19 mg/g) and P. biglobosa (4.5 mg/g). It is the same for the contents of anthocyanidins. Three plants studied, P. longifolia proved richest in polyphenols (condensed tannins, total flavonoids, anthocyanidins and anthocyanins) and A. difformis the less rich. This content of polyphenolic compounds would explain the test results of radical scavenging activities with an IC50 of 21.66 mg/mL for P. longifolia, 23.99 mg/mL for P. biglobosa and 26.5 mg/mL for A. difformis. The solid phase micro extraction (SPME) coupled with GC/MS allowed the unambiguous identification of volatile components of each of the three plants.
Keywords: Polyphenols; Radical scavenging activities; SPME; Anchomanes difformis; Parkia biglobosa; Polyalthia longifolia